MONITORING SYSTEMS DESIGN FOR EARLY DAMAGE DETECTION OF ELECTRIC MOTOR BASED COMPUTER - Tugino1, T; Harianto, H; Cahyo, Widian (ReTII, 2017)
Damage to the electric motor can be detected at an early stage of temperature and vibration. temperature and electric motor abnormal vibration occurs due to the damage including damage to the bearing, load imbalance, misalignment, insulation failure in the motor windings and others. This research aims to design of monitoring system for temperature and vibration analysis of electric motors based computer. This research can be used to help detect early occurrence of early damage to the electric motor that can lead to patterns of temperature and vibration and amplitude are likely to rise, so it can endorse the program of maintenance on the electric motor. The design consists of temperature and vibration sensors, sensor amplifier, data acquisition and computer programmed with Labview. After testing it was found that the tool has been able to work as expected. Testing patterns of temperature and vibration motor disorders tended to be higher than the motor works normally. temperature and vibration motors higher the bias caused by the motor load is not balanced, there is damage to the winding or mechanical damage. In testing shows that the temperature and vibration monitoring will be detected if there are irregularities in the motor which will cause a rise in temperature and vibration. If the rise exceeded the limit that has been setup then the tool will turn on alarm lights Keywords : early detection, damage, electric motor, monitoring system , computer